Patency of Individual and Sequential Coronary Artery Bypass in Patients with Ischemic Heart Disease: A Meta-analysis - Li,Zeshu (2019)
Abstract Objective: To evaluate the patency of individual and sequential coronary artery bypass in patients with ischemic heart disease. Methods: We searched PubMed, Cochrane Library, Excerpta Medica Database, and ClinicalTrials.gov databases for controlled trials. Endpoints included graft patency, anastomosis patency, occluded rates in left anterior descending (LAD) system and right coronary artery (RCA) system, in-hospital mortality, and follow-up mortality. Pooled risk ratios (RRs) and standardized mean difference (SMD) were used to assess the relative data. Results: Nine cohorts, including 7100 patients and 1440 grafts under individual or sequential coronary artery bypass. There were no significant differences between individual and sequential coronary artery bypass in the graft patency (RR=0.96; 95% CI=0.91-1.02; P=0.16; I2=87%), anastomosis patency (RR=0.95; 95% CI=0.91-1.00; P=0.05; I2=70%), occluded rate in LAD system (RR=1.03; 95% CI=0.92-1.16; P=0.58; I2=37%), occluded rate in RCA system (RR=1.36; 95% CI=0.72-2.57; P=0.35; I2=95%), in-hospital mortality (RR=1.57; 95% CI=0.92-2.69; P=0.10; I2=0%), and follow-up mortality (RR=0.96; 95% CI=0.36-2.53; P=0.93; I2=0%). Conclusion: No significant differences on clinical data were observed regarding anastomosis patency, occluded rate in LAD system, occluded rate in RCA system, in-hospital mortality, and follow-up mortality, indicating that the patency of individual and the patency of sequential coronary artery bypass are similar to each other.